2020
DOI: 10.1002/smll.202002063
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray‐Induced Growth Dynamics of Luminescent Silver Clusters in Zeolites

Abstract: In this work we used AlKα X-rays to drive the growth of luminescent silver clusters in zeolites.We tracked the growth of the silver species using Auger spectroscopy and fluorescence microscopy, by monitoring the evolution from their ions to luminescent clusters and then metallic, dark nanoparticles. We show that the growth rate in different zeolites is determined by the mobility of the silver ions in the framework and that the growth dynamics in calcined samples obeys the Hill-Langmuir equation for non-coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…This demonstrates the ionic state of silver clusters. 41,42 This result is also confirmed by the IR analysis, using CO as probe molecule, which demonstrates the presence of both metallic and ionic silvers (Figure S10). Therefore, based on these results and the TEM data we conclude that silver particles are in form of reduced Ag n + clusters with a partial cationic charge (n>).…”
Section: Materials Advances Accepted Manuscriptsupporting
confidence: 60%
“…This demonstrates the ionic state of silver clusters. 41,42 This result is also confirmed by the IR analysis, using CO as probe molecule, which demonstrates the presence of both metallic and ionic silvers (Figure S10). Therefore, based on these results and the TEM data we conclude that silver particles are in form of reduced Ag n + clusters with a partial cationic charge (n>).…”
Section: Materials Advances Accepted Manuscriptsupporting
confidence: 60%
“…It indicated that the growth rate of silver species follows a noncooperative Hill− Langmuir type behavior and is different in FAU zeolites, depending on the mobility of Ag + in the framework. 18 In addition, some controllable conditions like the silver loading degree, thermal treatment temperature, counterbalancing cations, hydration state, and formaldehyde adsorption also greatly influence the luminescence performance of Ag NCs, 3,7,9,17,19,20 which thus make the precise synthesis as well as the light emitting, sensing, and detecting applications of Ag NCs possible in zeolites. For example, studies about the effect of counterbalancing cations (such as Na + , Li + , K + , and Cs + ) on the luminescence properties of Ag NCs inside zeolites indicated that Ag NCs exhibited shifted emission wavelength in the presence of different co-cations and showed high emission intensity in the Li + -exchanged zeolites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The high-resolution XPS spectra of Ag 3d in Figure a show two binding energies near 368.6 and 374.6 eV, which can be ascribed to Ag 3d 5/2 and Ag 3d 3/2 , respectively. It has been proposed that the binding energy of Ag 3d 5/2 at 367.9–368.4 eV is attributed to Ag 0 and 367.6–368.5 eV belongs to Ag 2 O; thus, the binding energy of Ag 3d 5/2 alone cannot distinguish the silver species accurately because of the energy overlap. ,, In this case, the MNN Auger spectra of Ag, which can more sensitively detect the changes of chemical bonding environment, were measured and are shown in Figure b, which presents two broad bands near 348.0 and 353.0 eV, ascribed to Ag M 5 N 45 N 45 and Ag M 4 N 45 N 45 , respectively. ,, Based on the above XPS data, the Auger parameters (APs) were calculated through the sum of the binding energy of Ag 3d 5/2 and the kinetic energy of Ag M 4 N 45 N 45 (AP = Ag 3d 5/2 + Ag M 4 N 45 N 45 ) to quantify the chemical shift of the atomic orbitals. As listed in Table S3, the calculated APs of the silver species are 721.7 eV for 2LiY20Ag, 721.8 eV for NaY20Ag, and 722.1 eV for 2CaY20Ag, all of which exhibit a large chemical shift (3.0–5.0 eV) compared with silver metal or nanoparticles (AP = 726.0 eV) and a small chemical shift (1.0–2.0 eV) compared with silver ( I ) oxide (AP = 724.1 eV), indicating the formation of Ag NCs and the slight variations in the chemical bonding environment caused by different extra-framework cations in the FAU-Y zeolites. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, Ag NCs exhibit brighter emission in Li + partially exchanged LTA zeolites than in the Na + -type counterpart; the emission intensity of Ag NCs can be greatly improved by thermal treatment in FAU zeolites, and the optimized treatment temperature is related to the Ag + loading amount. Ag NCs formatted under a mild thermal activation may not be suitable for lighting applications, as they are not stable enough; however, they can be used for low-content formaldehyde detection . The LTA­(Li)-Ag composite was suggested for humidity sensor application due to its remarkable dynamic change in Ag NCs emission color depending on the hydration level. , Besides, because of their tunable emission in the whole visible range and high quantum yield, Ag NCs have also been employed as sensitizers for f–f transition rare-earth (RE) ions like Eu 3+ , Tb 3+ , and Dy 3+ to improve their excitation efficiency or realize white light and tunable emission. Furthermore, the growth dynamics of Ag NCs and the effect of RE dopants like Tb 3+ on the formation efficiency and chemical state of Ag NCs have been studied using the modified Auger parameter and fluorescence microscopy. , …”
Section: Introductionmentioning
confidence: 99%